Übersetzung als Kulturaustausch - Ozil, Seyda; Hofmann, Michael; Laut, Jens-Peter; Dayıoğlu-Yücel, Yasemin; Uca, Didem (Universitätsverlag Göttingen, 2019)
The contributions to this volume approach the subject of translation from a multitude of perspectives. They thus show how translations are not only closely connected with notions of language, literature, and cultural studies but also reciprocally influence societal and political circumstances as much as they are influenced by these.